Inheritance and Linkage of Virulence Genes in Chinese Predominant Race CYR32 of the Wheat Stripe Rust Pathogen Puccinia striiformis f. sp. tritici - Wang, Long; Zheng, Dan; Zuo, Shuxia; Chen, Xianming; Zhuang, Hua; Huang, Lili; Kang, Zhensheng; Zhao, Jie (Frontiers in Plant Science, 2018)
Puccinia striiformis f. sp. tritici (Pst) is the causal agent of stripe (yellow) rust on wheat. It seriously threatens wheat production worldwide. The obligate biotrophic fungus is highly capable of producing new virulent races that can overcome resistance. Studying the inheritance of Pst virulence using the classical genetic approach was not possible until the recent discovery of its sexual stage on barberry plants. In the present study, 127 progeny isolates were obtained by selfing a representative Chinese Yellow Rust (CYR) race, CYR32, on Berberis aggregate. The parental isolate and progeny isolates were characterized by testing them on 25 wheat lines with different Yr genes for resistance and 10 simple sequence repeat (SSR) markers. The 127 progeny isolates were classified into 27 virulence phenotypes, and 65 multi-locus genotypes. All progeny isolates and the parental isolate were avirulent to Yr5, Yr8, Yr10, Yr15, Yr24, Yr26, Yr32 and YrTr1; but virulent to Yr1, Yr2, Yr3, Yr4, Yr25, Yr44 and Yr76. The virulence phenotypes of the parental isolate to nine Yr genes (Yr6, Yr7, Yr9, Yr17, Yr27, Yr28, Yr43, YrA and YrExp2) and the avirulence phenotype to YrSP were found to be heterozygous. Based on the segregation of the virulence/avirulence phenotypes, we found that the virulence phenotypes to Yr7, Yr28, Yr43 and YrExp2 were controlled by a dominant gene; those to Yr6, Yr9 and YrA (Yr73, Yr74) by two dominant genes; those to Yr17 and Yr27 by one dominant and one recessive gene; and the avirulence phenotype to YrSP by two complementary dominant genes. Molecular mapping revealed the linkage of 10 virulence/avirulence genes. Comparison of the inheritance modes of the virulence/avirulence genes in this study with previous studies indicated complex interactions between virulence genes in the pathogen and resistance genes in wheat lines. The results are useful for understanding the plant-pathogen interactions and developing wheat cultivars with effective and durable resistance.